Short communication: A survey on parasitoids of rice pest insects in Sisophon, Northwest Cambodia - Long, Khuat Dang; Try, Yorn (Academia Journal of Biology, 2018)
Of the total nine hymenopteran parasitic wasps revealed from rice paddy in Sisophon, Northwest Cambodia, there are six larval braconid parasitoids: Apanteles cypris Nixon, Bracon onukii Watanabe, Dolochogenidea agilis Ashmead, Pentatermus striatus (Szepligeti), Taiwanhormius sp., Tropobracon luteus Cameron (Braconidae); two pupal ichneumonid species: Casinaria colacae Sonan, Xanthopimla flavolineata Cameron (Ichneumonidae), and one egg scelionid parasitoid: Telenomus rowani Gahan (Scelionidae). Additionally, all the species were recorded for the first time for Cambodia’s fauna.